First detection of insertion sequence element ISPa1328 in the oprD porin gene of an imipenem-resistant Pseudomonas aeruginosa isolate from an idiopathic pulmonary fibrosis patient in Marseille, France. (September 2015) - Al-Bayssari, C.; Valentini, C.; Gomez, C.; Reynaud-Gaubert, M.; Rolain, J.-M.
Abstract: We report here the first case of a carbapenem-resistant Pseudomonas aeruginosa clinical isolate harboring the insertion sequence (IS) element IS Pa 1328 in the oprD gene in an idiopathic pulmonary fibrosis patient in France previously treated with imipenem.